The bacterial intimins and invasins: a large and novel family of secreted proteins. - Jennifer C Tsai; Ming-Ren Yen; Rostislav Castillo; Denisse L Leyton; Ian R Henderson; Milton H Saier (PLoS ONE)
Background Gram-negative bacteria have developed a limited repertoire of solutions for secreting proteins from the cytoplasmic compartment to the exterior of the cell. Amongst the spectrum of secreted proteins are the intimins and invasins (the Int/Inv family; TC# 1.B.54) which are characterized by an N-terminal β-barrel domain and a C-terminal surface localized passenger domain. Despite the important role played by members of this family in diseases mediated by several species of the Enterobacteriaceae, there has been little appreciation for the distribution and diversity of these proteins amongst Gram-negative bacteria. Furthermore, there is little understanding of the molecular events governing secretion of these proteins to the extracellular milieu. Principal findings In silico approaches were used to analyze the domain organization and diversity of members of this secretion family. Proteins belonging to this family are predominantly associated with organisms from the γ-proteobacteria. Whilst proteins from the Chlamydia, γ-, β- and ε-proteobacteria possess β-barrel domains and passenger domains of various sizes, Int/Inv proteins from the α-proteobacteria, cyanobacteria and chlorobi possess only the predicted β-barrel domains. Phylogenetic analyses revealed that with few exceptions these proteins cluster according to organismal type, indicating that divergence occurred contemporaneously with speciation, and that horizontal transfer was limited. Clustering patterns of the β-barrel domains correlate well with those of the full-length proteins although the passenger domains do so with much less consistency. The modular subdomain design of the passenger domains suggests that subdomain duplication and deletion have occurred with high frequency over evolutionary time. However, all repeated subdomains are found in tandem, suggesting that subdomain shuffling occurred rarely if at all. Topological predictions for the β-barrel domains are presented. Conclusion Based on our in silico analyses we present a model for the biogenesis of these proteins. This study is the first of its kind to describe this unusual family of bacterial adhesins.